Changes in lactate, pyruvate and glucose levels in field hockey players under different training and match stimuli - Podgórski, Tomasz; Adrian, Jacek; Nowak, Aleksandra (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Lactate, pyruvate and glucose levels are the most common biochemical markers used for controlling training loads and physical efficiency of athletes. Each stage of a field hockey training cycle requires activation of a different metabolite responsible for physical exercise. Aim of Study. The aim of the study was to determine the biochemical response of field hockey players to different types of exercise in a training cycle in comparison to a real match. Material and Methods. Ten male university team field hockey players took part in the study. The players were examined six times during an annual training cycle. The examination consisted of the following tests: treadmill test (twice), 13 km running, interval training, spinning, and a real field hockey match. During the tests preand post-exercise capillary blood from a fingertip was collected to determine the lactate (La), pyruvate (Pa) and glucose levels using enzyme methods. Furthermore, bioelectrical impedance analysis (BIA) was carried out four times during the annual training cycle. Results. Each exercise test increased the La and Pa concentrations, however, the glucose level was raised only during the treadmill tests. The 13 km running test and interval training results were statistically different. The most essential changes of La and Pa concentrations were noted between the treadmill tests and the match. Conclusions. The aim of field hockey training is to prepare players to meet match requirements. The analysis of players’ metabolic responses to different kinds of training indicates that a match effort is similar to 13 km running and physiologically close to interval training.